Adjuvant system AS01: helping to overcome the challenges of modern vaccines - Arnaud M. Didierlaurent; Béatrice Laupèze; Alberta Di Pasquale; Nadia Hergli; Catherine Collignon; Nathalie Garçon (Expert Review of Vaccines, 2017)
Introduction: Adjuvants are used to improve vaccine immunogenicity and efficacy by enhancing antigen presentation to antigen-specific immune cells with the aim to confer long-term protection against targeted pathogens. Adjuvants have been used in vaccines for more than 90 years. Combinations of immunostimulatory molecules, such as in the Adjuvant System AS01, have opened the way to the development of new or improved vaccines. Areas covered: AS01 is a liposome-based vaccine adjuvant system containing two immunostimulants: 3-O-desacyl-4ʹ-monophosphoryl lipid A (MPL) and the saponin QS-21. Here we describe studies investigating the mode of action of AS01, and consider the role of AS01 in enhancing specific immune responses to the antigen for selected candidate vaccines targeting malaria and herpes zoster. The effects of AS01 are rapid and transient, being localized to the injected muscle and draining lymph node. AS01 is efficient at promoting CD4+ T cell-mediated immune responses and is an appropriate candidate adjuvant for inclusion in vaccines targeting viruses or intracellular pathogens. Expert commentary: AS01 activity to enhance adaptive responses depends on synergistic activities of QS-21 and MPL. AS01 adjuvantation shows good prospects for use in new vaccines targeted to populations with challenging immune statuses and against diseases caused by complex pathogens.